Smart trends in information technology and computer communications : second International Conference, SmartCom 2017, Pune, India, August 18-19, 2017, Revised selected papers /: second International Conference, SmartCom 2017, Pune, India, August 18-19, 2017, Revised selected papers. (2018) - Unknown
No abstract available